2019
DOI: 10.1002/ijc.32759
|View full text |Cite
|
Sign up to set email alerts
|

Intravital imaging of vascular anomalies and extracellular matrix remodeling in orthotopic pancreatic tumors

Abstract: Pancreatic cancers, both adenocarcinomas and endocrine tumors are characterized by varying levels of aberrant angiogenesis and fibrotic microenvironment. The difficulty to deliver drugs and treat the disease has been attributed in part to the vascular architecture and tissue/ECM density. Here we present longitudinal three‐dimensional intravital imaging of vascular and tumor microenvironment remodeling in spontaneous transgenic tumors (RIP1‐Tag2 insulinomas) and orthotopically injected tumors (KPC adenocarcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…While recent advances have enabled intravital imaging of the pancreas, existing designs are still limited in either stability for long-term time-lapse imaging on the minutes time scale, or their ability to accommodate pancreata of a variety of sizes (e.g. healthy versus tumour bearing) [8,14,42].…”
Section: Discussionmentioning
confidence: 99%
“…While recent advances have enabled intravital imaging of the pancreas, existing designs are still limited in either stability for long-term time-lapse imaging on the minutes time scale, or their ability to accommodate pancreata of a variety of sizes (e.g. healthy versus tumour bearing) [8,14,42].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of the TME, vascular remodeling has received particular attention as it impacts tumor nutrition, oxygenation, dissemination, and the recruitment of immune components. Quantitative assessments of the extent of tumor vascularization can be readily achieved by both tissue clearing and IVM, and have shown that several tumor types share a tendency to increase the vascular density within their mass ( 33 , 49 , 121 ). In some cancers the angiogenic capabilities may extend to lymphangiogenesis, as seen in pancreatic cancer ( 62 ).…”
Section: Applications Of Volume Imaging To Visualize Cell-tme Interac...mentioning
confidence: 99%
“…Several pharmacological and physical strategies aiming at modulating the TME to alleviate tumor fibrosis have been shown to improve the delivery and efficacy of drugs and drug nanoformulations. [13][14][15] Many TME remodeling strategies have specifically focused on nanomedicine formulations, such as liposomes and micelles. [16][17][18][19] Nanomedicines can accumulate in tumors relatively effectively and selectively, thereby improving therapeutic performance and minimizing side effects.…”
Section: Introductionmentioning
confidence: 99%